The Gray Digital Divide in Social Networking Site Use in Europe: Results From a Quantitative Study. (April 2022) - Sala, Emanuela; Gaia, Alessandra; Cerati, Gabriele
Social networking sites (SNSs) might be important tools to contrast social exclusion in old age. However, the so-called gray digital divide (GDD) may undermine the potentialities of SNSs. Despite its relevance, there is very little research, which documented the characteristics of the digital divide in SNS use among the old-age population in Europe. Drawing on the " material access in resources and appropriation " theory developed by van Dijk, this work contributes to consolidate the body of research, documenting the nature of the GDD in SNS use in Europe and evaluating the role that older people's categorical, personal, and positional characteristics together with ICT characteristics play in gaining access to digital technologies. We analyze data from the 2013–2016 Eurostat Community Statistics on Information Societies (CSIS) survey and perform bivariate and multilevel regression analysis. Key findings are (i) the persistence of the intergeneration digital divide in old age together with the marked cross-countries differences in SNS use across European countries and over time and (ii) the stability over old-age generations, countries, and time of the positional categories associated with SNS use in old age, providing further empirical support to van Dijk's theory.